2016
DOI: 10.15547/ast.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigation and fertilization on soil microorganisms

Abstract: The purpose of this study is to determine the influence of nitrogen fertilization and irrigation on the total count of aerobic mesophilic microorganisms, moulds and yeasts in the soil. The experiment was conducted in three variants and samples were taken as follows: from irrigated and fertilized furrow; from irrigated non-fertilized furrow and from furrow without irrigation and fertilization. For determination of total number of mesophilic aerobic microorganisms, moulds and yeasts the samples were diluted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, irrigation can improve the soil moisture conditions and meet the demands for crop growth, which is general use is in the arid and semi-arid region of China. However, few studies have investigated the effects on the microbial community dynamics of land management based on irrigation and nitrogen and phosphorus chemical fertilizer incorporate (Dinev et al, 2016).…”
mentioning
confidence: 99%
“…In addition, irrigation can improve the soil moisture conditions and meet the demands for crop growth, which is general use is in the arid and semi-arid region of China. However, few studies have investigated the effects on the microbial community dynamics of land management based on irrigation and nitrogen and phosphorus chemical fertilizer incorporate (Dinev et al, 2016).…”
mentioning
confidence: 99%
“…In the study by Yan et al [ 38 ], ammonification bacteria significantly increased, and N-fixing bacteria significantly decreased with precipitation reduction. Dinev et al [ 39 ] showed that fertilization has the strongest multiplication effect on the number of aerobic mesophilic microorganisms in the soil, whereas irrigation has no statistically significant impact. In the study by Jiao et al [ 40 ], with the increase in soil moisture, the dominant bacterial species shifted from Actinobacteria to Alphaproteobacteria and Acidobacteria.…”
Section: Discussionmentioning
confidence: 99%